Learning hope and optimism: classmate experiences and adolescent development. Issue 5 (12th March 2019) - Fletcher, Jason M.; Kim, Jinho
ABSTRACT: This article explores individual and contextual factors related to the development of hopeful attitudes during adolescence using a nationally representative study. A key focus is on the experiences of mistreatment by adults, both for the adolescent and his/her classmates. While all types of individual experiences with mistreatment reduce adolescent hopefulness, mistreatment domains most likely to be visible (i.e. physical abuse) by classmates also reduce adolescent hopefulness. This relationship is robust to the inclusion of more general environmental factors through school-level fixed effects, suggesting both a causal explanation and a typically unmeasured spillover effect of violence against children. Other types of mistreatment, such as neglect and material hardship, do not show spillover effects.